Pengembangan E-modul Fisika Terintegrasi Model PBL dan Etnosains untuk Meningkatkan Keterampilan Abad 21 Siswa - Anisa Dwita Fitri; Asrizal (Jurnal Penelitian Pendidikan IPA, 2023)
The 21’st century learning should be able to build students’ abilities comprehensively. Students are expected to have 21’st century learning skills known as 4C skills, namely critical thingking, creative thingking, collaboration and communication. Meaningful learning is needed to improve students’ 21st century skills, such as integrated physics learning with ethnoscience. Ethnoscience related to local cultural concepts integrated into e-module can be used as a learning resource. The purpose of this study is to describe the results of the preliminary research and development stages of the physic e-module integrated with PBL model and ethnoscience to improve students’ 21 Century skills. This study is a research and development (R&D) type and the Plomp model. The instruments used were teacher and student interview sheets, self-evaluation sheets, validity and practicality questionnaires. Based on data analysis, the results of validity testing in the valid category with an average value 0.94. Then, the results of practicality testing in the very practical category with an average value 90.09. It can be concluded, the physics e-module integrated with PBL model and ethnoscience to improve students' 21st century skills is valid and practical for use in the learning process.